A method for preparing graphene material using catalytic oil slurry
Through the heat condensation and extraction treatment of catalytic oil slurry, combined with the carbonization treatment of nanometal oxide template agent, thin-layer graphene material was successfully prepared, solving the problem that it is difficult to prepare thin-layer graphene in heavy oils, and realizing graphene High added value-added green utilization and large-scale production.
Patent Information
- Application Number
- CN202111212713.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-10-18
Smart Images

Figure CN115991469B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the intersecting field of petrochemical industry and carbon nanomaterial science, and relates to a method for preparing porous graphene material by taking catalytic oil slurry as raw material. Background Art
[0002] Graphene is a two-dimensional material with a hexagonal honeycomb lattice composed of a single layer of carbon atoms. Due to its best mechanical, optical and electrical properties, it is called the "king of new materials" and has good application prospects in many fields such as transistors, touch screens, sensors, new energy, solar energy, catalysis, etc. Researchers use various methods to prepare graphite materials. The preparation of graphene can be attributed to two technical strategies: "Top-down" and "Bottom-up". The "Top-down" method is generally prepared by chemical oxidation-reduction method from natural graphite or carbon sources with graphite structure, which is easy to achieve mass production. However, the structure of the graphene material synthesized by severe intercalation and etching under harsh conditions is severely damaged, causing its conductivity, mechanical strength and thermal properties to drop sharply. In addition, the use of a large number of strong oxidizing agents also makes the process cumbersome, costly and environmentally harmful; the "Bottom-up" technology is generally to grow graphene materials after hydrocarbons are cracked into single carbon atoms under the catalysis of transition metals. The graphene obtained by this method has a relatively complete structure and excellent electrical and thermal properties, but due to the limitations of the process, it is difficult to achieve continuous mass production.
[0003] From the above, we can see that establishing a new continuous and low-cost preparation technology is the key to the rapid development of graphene materials. In addition, since the research and application of graphene in China are mainly concentrated in the fields of energy storage and composite materials, the production cost, quality and scale of graphene are the key to its large-scale application.
[0004] At present, the large-scale preparation of graphene in my country basically adopts the redox method. The redox method mainly relies on graphite and graphite oxide as carbon sources. The process is complicated and requires a large amount of corrosive strong acid. In addition, the graphene produced has more heteroatoms and thicker graphene layers, which is not graphene in the strict sense. Therefore, it is urgent to develop a method for mass preparation of graphene.
[0005] As one of the main energy sources in my country, oil plays a key role in the national economy. Heavy crude oil (density of 0.93 g / cm at 20 °C) 3The proportion of heavy oil (heavy oil) is more than 50wt%. The high value-added green utilization of heavy oil has become a global problem, and it is urgent to develop new technologies for its green high value-added utilization. Since heavy oil contains a large amount of polycyclic aromatic hydrocarbons, which are the basic components of carbon materials, some domestic researchers have conducted relevant research on the preparation of porous carbon materials such as graphene using heavy oil as raw materials.
[0006] Chinese patent CN104591184A discloses a method for preparing a shell-shaped mesoporous carbon material for supercapacitors, using petroleum asphalt as a carbon source, nano zinc oxide as a template, and potassium hydroxide as an activator. After grinding and mixing the three, carbonization treatment is carried out within a certain temperature range to prepare a mesoporous carbon material with a porous structure. Chinese patent CN106185890A discloses a method for preparing a porous graphene-like material, using coal tar as a raw material, using ammonium inorganic salt as a pore-forming agent, carbonization treatment is carried out within a certain temperature range, soaking and washing after cooling, and drying in a vacuum drying oven to obtain a porous graphene-like material. Chinese patent CN104098091B discloses a method for preparing a porous graphene material for supercapacitors, using coal tar as a carbon source, nano calcium carbonate as a template, and potassium hydroxide as an activator. After mixing the three, carbonization treatment is carried out under normal pressure or negative pressure to directly obtain a porous graphene material.
[0007] At present, the preparation method of porous graphene mainly uses graphite and graphite oxide as carbon sources. Some researchers have prepared graphene and other carbon materials by developing heavy oil carbon sources and new process paths. Among them, heavy oil mainly revolves around petroleum asphalt and coal asphalt, and the template agent usually uses salt or zinc oxide as a hard template. It can be seen from the above patents that when petroleum asphalt or coal asphalt is used directly as a carbon source, the graphene material obtained usually has a thicker layer; the use of salt hard templates usually causes the graphene material to be lamellar and thicker, and some structures are porous carbon materials, most of which are thicker block structures, and thin-layer graphene materials cannot be obtained.
[0008] This is because heavy oil is a complex mixture of many aliphatic hydrocarbons, cycloalkanes and polycyclic aromatic hydrocarbons. Its composition and structure are complex and multi-layered. There are a large number of hydrocarbon compounds and non-hydrocarbon compounds, as well as colloidal and asphalt-like supramolecular aggregates, and there are multi-scale molecular structures. Although the heavy oil component contains a large number of polycyclic aromatic units, as the degree of polycondensation deepens during the synthesis of carbon materials, the strong π-π force drives the heavy oil molecules to stack to form infusible and insoluble supramolecular clusters, causing the viscosity of the heavy oil to increase rapidly when heated, and quickly coke, and it is impossible to ensure the acquisition of a thin layer structure during carbonization; at the same time, the large number of side branches on the aromatic molecules will hinder the orderly rearrangement of the heavy oil molecules during the carbonization process, seriously affecting the microstructure of the carbon material, and thus it is extremely difficult to control the structure of the carbon material. Summary of the invention
[0009] In view of the problem that the existing technology cannot obtain thin-layer graphene materials from heavy oil, the present invention proposes a method for preparing graphene materials from catalytic oil slurry. The method uses catalytic oil slurry as raw material, firstly regulates the structure of the catalytic oil slurry, effectively obtains the aromatic-rich molecules therein, and prepares three-dimensional thin-layer graphene carbon materials by reasonably regulating the molecular structure of polycyclic aromatic hydrocarbons, thereby realizing the high-value-added green utilization of heavy oil.
[0010] The present invention provides a method for preparing graphene material from catalytic oil slurry, comprising the following steps:
[0011] (1) subjecting the catalytic oil slurry to a thermal polycondensation treatment under the protection of an inert gas atmosphere, and taking out the liquid phase as the thermal polycondensation oil after cooling;
[0012] (2) mixing the polycondensed oil with an extractant for extraction and separation, allowing the mixture to stand for stratification after extraction and taking the lower layer liquid, and evaporating the extractant in the lower layer solution to obtain the enriched aromatic oil;
[0013] (3) fully mixing the enriched aromatic oil and the template in the presence of an organic solvent as an auxiliary agent, and then carbonizing the mixture in an inert gas atmosphere;
[0014] (4) The carbonized product obtained in step (3) is subjected to acid washing to remove the template agent, washed with deionized water and then dried to obtain a porous graphene material.
[0015] The catalytic oil slurry in step (1) of the present invention includes the oil slurry thrown out under different catalytic cracking process conditions. The present invention does not particularly limit the composition of the catalytic oil slurry. The thermal polycondensation process is particularly suitable for catalytic oil slurry with low aromatic content and high saturated and asphaltene content; for oil slurry with high aromatic content, the thermal polycondensation reaction time will be shortened and the temperature will be reduced.
[0016] In the method of the present invention, preferably, the drying in step (4) is vacuum drying.
[0017] The method of the present invention is preferably performed with stirring in step (1), wherein the stirring speed is not less than 150 rpm, preferably greater than 200 rpm, and more preferably the stirring speed is 200 to 500 rpm.
[0018] The method of the present invention is preferably such that the saturated content in the heat-condensation polyol is less than 18wt%, the aromatic content is greater than 45wt%, the fraction below 520°C is greater than 50wt%, and no special requirements are made for the asphaltene and colloid content.
[0019] The method of the present invention, wherein preferably, the conditions of the heat polycondensation treatment are: temperature 380-420°C, pressure 2-7MPa, time 2-10 hours; further preferably, the temperature is 380-400°C; further preferably, the temperature raising program of the heat polycondensation treatment is any one of the following:
[0020] (1) 5~10℃·min -1 Heating to 350℃, at 3℃·min -1 Rapidly heat to 380°C within 10 minutes, keep warm for 6 to 10 hours, and keep the pressure at 3 to 5 MPa;
[0021] (2) 5~10℃·min -1 Heating to 350℃, 5℃·min -1 Rapidly heat to 400°C within 10 minutes, keep warm for 2 to 6 hours, and keep the pressure at 2 to 6 MPa;
[0022] (3) 5~10℃·min -1 Heating to 350℃, at 7℃·min -1 Rapidly heat to 420℃ within 10min, keep warm for 1.5-3h, pressure 2-4MPa.
[0023] The method of the present invention, wherein preferably, the extractant comprises at least one of furfural, n-octane and cyclohexane, further preferably, the extractant consists of furfural and n-octane, further preferably, the mass ratio of n-octane:furfural is 1:2 to 2:2, further preferably 1.5:2.
[0024] In the method of the present invention, preferably, the mass ratio of the extractant to the thermal polycondensation oil is 1:1 to 2.5:1, and more preferably 1.25:1 to 2:1.
[0025] The method of the present invention is preferably performed at a temperature of 50 to 90°C, more preferably 60 to 70°C.
[0026] The method of the present invention is preferably such that, in the enriched aromatic oil, the saturated fraction is less than 5wt%, the aromatic fraction is greater than 80wt%, and the asphaltenes are less than 2wt%.
[0027] In the method of the present invention, it is preferred that the template is metal oxide nanoparticles, more preferably nano iron oxide, nano magnesium oxide or nano zinc oxide, and the particle size is 30 to 200 nm, more preferably 80 to 150 nm.
[0028] In the method of the present invention, it is preferred that the mass ratio of the template to the enriched aromatic oil is 3:1 to 5:1.
[0029] The method of the present invention, wherein preferably, the organic solvent is selected from one of toluene, xylene, carbon disulfide and carbon tetrachloride, further preferably toluene, and further preferably, the volume ratio of the organic solvent to the enriched aromatic oil is 0.3 to 1.0:1.
[0030] The method of the present invention is preferably such that the heating rate of the carbonization treatment is 5 to 10°C / min, the carbonization temperature is 700 to 900°C, and the carbonization time is 1 to 3h.
[0031] In the method of the present invention, preferably, the inert gas is nitrogen or argon.
[0032] The method of the present invention is preferably that the acid used for pickling is hydrochloric acid, sulfuric acid or nitric acid, and further preferably, the mass ratio of the acid to the template is 3:1 to 1:1.
[0033] The method of the present invention is preferably that the porous graphene material is a three-dimensional structure in the form of a porous thin shell with a wall thickness of only 2 to 4 nm and a number of layers of less than 10.
[0034] Specifically, the technical scheme of the method for preparing graphene material from catalytic oil slurry of the present invention is as follows:
[0035] (1) The catalytic oil slurry is placed in a high-pressure reactor equipped with a stirring device, stirred and heated under the protection of an inert gas atmosphere, and maintained at a temperature of 380-420° C. and a pressure of 2-7 MPa for 2-10 hours for thermal polycondensation treatment. After cooling, stirring is stopped and the liquid phase is taken out as the thermal polycondensation oil.
[0036] (2) mixing the heat-condensed oil with an extractant and performing solvent extraction, allowing the mixture to stand for stratification after extraction, taking a lower layer of liquid, and evaporating the extractant in the lower layer of liquid to obtain an enriched aromatic oil;
[0037] (3) fully mixing the enriched aromatic oil and the nano metal oxide template in the presence of an organic solvent as an auxiliary agent, and then subjecting the mixture to a high-temperature carbonization treatment in an inert gas atmosphere;
[0038] (4) The obtained carbonized product is subjected to acid washing to remove the template agent, washed with deionized water and then dried in a vacuum oven to obtain a porous graphene material.
[0039] The purpose of stirring in step (1) of the present invention is mainly to ensure uniform heat transfer and prevent rapid coking at some locations due to uneven heating. The stirring speed is usually not less than 150 rpm, preferably greater than 200 rpm, and more preferably 200 to 500 rpm. At this stirring speed, uniform heat transfer can be ensured without splashing the oil phase due to excessive stirring speed.
[0040] The optimal heat polycondensation treatment conditions for step (1) of the present invention are:
[0041] 5~10℃·min -1 Heating to 350℃, at 3℃·min -1 Rapidly heat to 380℃ within 10min, keep warm for 6-10h, pressure 3-5MPa; can also be:
[0042] 5~10℃·min -1 Heating to 350℃, 5℃·min -1 Rapidly heat to 400℃ within 10min, keep warm for 2-6h, pressure 2-6MPa; can also be:
[0043] The temperature was raised to 350℃ at 5~10℃·min-1 and then to 7℃·min-1. -1 Rapidly heat to 420°C within 10 minutes, keep warm for 2 hours, and the pressure is 3 MPa.
[0044] The extractant recommended in step (2) of the present invention is a mixed dual solvent extractant of furfural and n-octane. The dual solvent extractant can efficiently separate the saturated and aromatic components in the polycondensed aromatic oil, while a single solvent extractant is difficult to separate the two phases.
[0045] The extraction temperature in step (2) of the present invention is 50-90°C, and the recommended optimal temperature range is 60-70°C; the recommended extractant mixing ratio is 1:2-2:2 of n-octane:furfural, and the recommended optimal ratio is 1.5:2; the recommended agent-oil ratio is 1:1-2.5:1, and the recommended optimal ratio is 1.25:1-2:1. The above preferred process parameters are intended to increase the yield of the extracted enriched aromatic oil.
[0046] The present invention recommends that the conditions for evaporating the extractant in the lower solution in step (2) are oil bath heating, the temperature is slowly raised to 120-140° C., the vacuum degree is maintained at 100 Pa-200 Pa, and the temperature is slowly raised during the whole process to prevent violent boiling.
[0047] The composition of the enriched aromatic oil obtained in step (2) of the present invention is that the saturated fraction is less than 5wt%, the aromatic fraction is greater than 80wt%, and the asphaltenes are less than 2wt%, and no special requirements are made on the colloid. The higher the aromatic fraction, the less asphaltenes and saturated fractions, the easier it is to control the carbonization forming, and the thinner the prepared carbon layer.
[0048] In step (3) of the present invention, the nano metal oxide template refers to one of nano iron oxide, nano magnesium oxide or nano zinc oxide, and its particle size is preferably 30 to 200 nm, and more preferably 80 to 150 nm. Nano metal oxide particles with too small particle size are easy to agglomerate and difficult to mix with the oil phase. Metal oxide particles with a particle size exceeding 200 nm are easy to form carbon blocks during the carbonization process.
[0049] In the present invention, when the enriched aromatic oil and the nano metal oxide template are fully mixed in step (3), it is best to also use an organic solvent as an auxiliary agent to improve the mixing effect of the template and the enriched aromatic oil and ensure that the template is evenly dispersed in the oil phase. The recommended solvent is one of hydrocarbon solvents such as toluene, xylene, carbon disulfide and carbon tetrachloride. Considering the dissolution effect, toluene solvent is the best. The recommended addition amount is an organic solvent: enriched aromatic oil volume ratio of 0.5:1. The organic solvent needs to be evaporated before carbonization, and the organic solvent can be recovered and recycled.
[0050] In the present invention, the heating rate of high-temperature carbonization in step (3) is controlled at 5 to 10°C / min. Slow carbonization helps to reduce the structural defects of the carbon layer. The carbonization temperature is 700 to 900°C and the carbonization time is 1 to 3 hours. The higher the carbonization temperature and the longer the time, the higher the degree of graphitization. No optimal recommendation is made for the carbonization temperature and time.
[0051] The present invention recommends that steps (1) thermal polycondensation of the catalytic oil slurry and (3) carbonization of the mixture of the enriched aromatic oil and the template agent be carried out under an inert atmosphere, wherein the inert gas may be nitrogen or argon.
[0052] In the present invention, the template is removed by pickling in step (4), and the acid is preferably hydrochloric acid, sulfuric acid or nitric acid. Hydrochloric acid is preferred, and the deionized water consumed by pickling to remove chloride ions is relatively minimal. The amount of acid added varies depending on the acid and template used, and the preferred addition ratio is a hydrochloric acid: iron oxide mass ratio of 1.5:1, a hydrochloric acid: magnesium oxide mass ratio of 2:1, and a hydrochloric acid: zinc oxide mass ratio of 1:1.
[0053] The beneficial effects of the present invention are as follows:
[0054] (1) Catalytic oil slurry is an important by-product in the process of petroleum refining, with huge annual output and complex composition. Conventional petroleum refining technologies such as atmospheric and vacuum distillation and catalytic cracking are difficult to efficiently and cleanly convert it. In view of the characteristics of catalytic oil slurry, the present invention uses catalytic oil slurry as raw material, and efficiently separates the aromatic components therein through heat treatment and solvent extraction treatment. The treated catalytic oil slurry is used as a carbon source, and nano-metal oxides are used as templates and pore-forming agents. Graphene materials with a thin layer of three-dimensional structure are prepared through carbonization treatment in an inert atmosphere. In addition, the method has a simple process, low raw material price, and controllable structure of the graphene material, which has a good market prospect for large-scale application.
[0055] (2) The method of the present invention regulates the molecular structure of the catalytic oil slurry through thermal polycondensation treatment, so that the saturated side chains that are easy to crack are broken and removed, thereby reducing the content of saturated components; the large molecular weight polycyclic aromatic hydrocarbons with attached cycloalkane rings and side branches that are easy to crack are further broken to form small molecular weight aromatic hydrocarbons, and the high-condensation-degree large molecular weight polycyclic components that are easy to coke are coked, thereby increasing the overall aromatic content.
[0056] (3) The method of the present invention further enriches aromatics through solvent extraction, and uses the extracted oil, i.e., aromatics-enriched oil, as a carbon source to improve the reactivity of the raw material molecules in preparing graphene materials. By mixing with a hard template, the aromatic molecules are self-assembled and grown into carbon materials through the skeleton and growth sites provided by the hard template agent during high-temperature treatment, and finally the template agent is removed by acid washing to obtain a three-dimensional structured thin-layer graphene material.
[0057] (4) The present invention uses catalytic oil slurry as raw material, which is abundant in source, cheap and easy to obtain. The obtained graphene material has a three-dimensional shell structure and a thin carbon layer. The present invention is expected to realize the high value-added industrial production and application of catalytic oil slurry, and provide new raw materials and methods for the preparation of three-dimensional graphene materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1a This is a scanning electron microscope image of the porous graphene material of Example 1;
[0059] Figure 1b , Figure 1c-1 , Figure 1c-2 This is a transmission electron microscope image of the porous graphene material of Example 1;
[0060] Figure 2a This is a scanning electron microscope image of the porous graphene material of Example 2;
[0061] Figure 2b , Figure 2c-1 , Figure 2c-2 This is a transmission electron microscope image of the porous graphene material of Example 2;
[0062] Figure 3a This is a scanning electron microscope image of the porous graphene material of Example 3;
[0063] Figure 3b , Figure 3c-1 , Figure 3c-2 This is a transmission electron microscope image of the porous graphene material of Example 3;
[0064] Figure 4a This is a scanning electron microscope image of the porous graphene material of Example 4;
[0065] Figure 4b , Figure 4c-1 , Figure 4c-2This is a transmission electron microscope image of the porous graphene material of Example 4;
[0066] Figure 5a This is a scanning electron microscope image of the porous graphene material of Example 5;
[0067] Figure 5b , Figure 5c-1 , Figure 5c-2 This is a transmission electron microscope image of the porous graphene material of Example 5;
[0068] Figure 6 This is a scanning electron microscope image of the porous graphene material of comparative example 4. DETAILED DESCRIPTION
[0069] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.
[0070] The catalytic cracking slurry raw material comes from the slurry thrown out of the catalytic cracking unit of PetroChina Liaohe Petrochemical Company. Its four components are: 44.64wt% saturates, 35.23wt% aromatics, 19.49wt% colloids, and 0.64wt% asphaltenes, and is used in Examples 1-7.
[0071] Oil composition analysis: The crude oil, "thermal polycondensation oil" and "enriched aromatics oil" were analyzed for their four-component composition by rod thin-layer chromatography. The crude oil and "thermal polycondensation oil" were also specially analyzed for their fraction content before 520°C by simulated distillation.
[0072] Sample structure analysis and results: The prepared graphene carbon material was subjected to scanning electron microscopy analysis to observe the morphology and transmission electron microscopy analysis to observe the thickness of the layer. The scanning electron microscopy results and transmission electron microscopy results of the samples of Examples 1-5 are shown in Figures 1-5.
[0073] Example 1
[0074] Step 1: High-temperature pretreatment of crude oil (i.e., thermal polycondensation treatment). Take 520 g of catalytic cracking oil slurry and put it into a high-temperature reactor. Raise the temperature to 380°C at 5°C / min under nitrogen atmosphere and maintain for 6 hours. Control the pressure at 5MPa. Release the pressure after the reaction is completed, and take out the liquid phase as the thermal polycondensation oil product after the temperature cools down.
[0075] Step 2: Solvent extraction. The extractant is mixed at a mass ratio of n-octane to furfural of 1.25:2; the heat-condensed oil and the extractant are stirred and mixed at a mass ratio of 1:1, and fully mixed at 50°C and allowed to stand for stratification. The lower layer of extractant is slowly heated to 140°C and the "enriched aromatic oil" is obtained under a vacuum degree of 150Pa.
[0076] Step 3: Template-induced carbonization treatment. Using toluene as solvent, fully mix the "enriched aromatic oil" and the nano-iron trioxide template agent in a mass ratio of 1:3, wherein the volume ratio of aromatic-enriched oil to toluene solvent is 1:0.5, and the particle size of nano-iron trioxide is 90nm. After mixing evenly, transfer the solid-liquid phase mixture to a rotary evaporator with a vacuum degree of 250Pa, slowly heat it to 100°C to evaporate the toluene solvent, and take out the solid mixture. Place the solid mixture in a porcelain boat and transfer it to a tubular furnace for carbonization treatment. Heat it to 800°C at 5°C / min under a nitrogen atmosphere and keep it for 1h. Take out the product after cooling it to room temperature.
[0077] Step 4: Pickling, water washing, and vacuum drying to obtain graphene material. The pickling conditions are hydrochloric acid: nano-iron trioxide mass ratio of 1.5:1, heating to 50°C, stirring at 500rpm for 1h. The water washing process is to repeatedly wash the product with deionized water until the pH of the water washing liquid is 7. After vacuum drying, a porous thin-layer graphene material is obtained.
[0078] The obtained porous graphene was analyzed by electron microscope scanning and observed by transmission electron microscope. Figure 1a to Figure 1c-2 As shown, from Figure 1a and Figure 1b It can be seen that the porous graphene generated by the "aromatics-enriched oil" used in this example under the carbonization induced by the nano-iron trioxide hard template agent presents a foam-like hollow three-dimensional shell structure, in which the pore structure is more obvious; through further magnification observation, such as Figure 1c-1 and Figure 1c-2 It can be more clearly seen that the thickness of the thin layer is between 2-4nm.
[0079] Example 2
[0080] Step 1: High-temperature pretreatment of crude oil. Take 520g of catalytic cracking oil slurry and put it into a high-temperature reactor. Raise the temperature to 380℃ at 5℃ / min and maintain for 10h under nitrogen atmosphere. Control the pressure at 3MPa. Release the pressure after the reaction is completed. After the temperature cools down, take out the liquid phase as the thermal polycondensation oil product.
[0081] Step 2: Solvent extraction. The extractant is mixed at a mass ratio of n-octane to furfural of 1.25:2; the heat-condensed oil and the extractant are stirred and mixed at a mass ratio of 1:1.25, and fully mixed at 60°C and allowed to stand for stratification. The lower layer of the extract is slowly heated to 140°C and the "enriched aromatic oil" is obtained under a vacuum of 150Pa.
[0082] Step 3: Template-induced carbonization treatment The same method as the third step in Example 1 was used, except that the hard template used was nano zinc oxide with a particle size of 100 nm.
[0083] Step 4: Pickling, water washing and vacuum drying to obtain graphene material. The same method as the fourth step in Example 4 is implemented, except that the mass ratio of hydrochloric acid to zinc oxide added during pickling is 1:1.
[0084] The obtained porous graphene was analyzed by electron microscope scanning to observe the morphology and transmission electron microscope to observe the thickness of the sheet. The results are as follows: Figure 2a to Figure 2c-2 As shown, from Figure 2a and Figure 2b It can be seen from the figure that the porous graphene generated by the "aromatic-enriched oil" used in this example under the carbonization induced by the nano-zinc oxide hard template also presents a rectangular hollow structure, with fewer wrinkles and smoother layers, and its pore size is significantly larger; through further magnification observation, such as Figure 2c-1 and Figure 2c-2 It can be more clearly seen that the thickness of the thin layer is also between 2-4nm.
[0085] Example 3
[0086] Step 1: High-temperature pretreatment of crude oil. Take 520g of catalytic cracking oil slurry and put it into a high-temperature reactor. Raise the temperature to 400℃ at 5℃ / min and maintain for 2h under nitrogen atmosphere. Control the pressure at 6MPa. Release the pressure after the reaction is completed. After the temperature cools down, take out the liquid phase as the thermal polycondensation oil product.
[0087] Step 2: Solvent extraction. The extractant is mixed at a mass ratio of n-octane to furfural of 1.25:2; the heat-condensed oil and the extractant are stirred and mixed at a mass ratio of 1:1.5, and fully mixed at 60°C and allowed to stand for stratification. The lower layer of extractant is slowly heated to 140°C and the "enriched aromatic oil" is obtained under a vacuum degree of 150Pa.
[0088] Step 3: Template-induced carbonization treatment: The same method as the third step in Example 1 is used, except that the "enriched aromatic oil" and the nano-iron trioxide template are fully mixed in a mass ratio of 1:5.
[0089] Step 4: Acid washing, water washing and vacuum drying to obtain graphene material. The same method as the fourth step in Example 1 is used.
[0090] The obtained porous graphene was subjected to scanning electron microscope analysis to observe the morphology and transmission electron microscope to observe the thickness of the sheet. The results are shown in FIG3. Figure 3a and Figure 3b It can be seen from the figure that the porous graphene generated by the "aromatic-enriched oil" used in this example under the carbonization induced by the nano-iron trioxide hard template with a larger amount (1:5) of the addition presents a denser foam-like hollow three-dimensional shell structure, with more wrinkles and thinner layers, and the pore structure is more obvious; through further magnification observation, such as Figure 3c-1 and Figure 3c-2It can be more clearly seen that the thickness of the thin layer is between 2-3nm.
[0091] Example 4
[0092] Step 1: High-temperature pretreatment of crude oil. Take 520g of catalytic cracking oil slurry and put it into a high-temperature reactor. Raise the temperature to 400℃ at 5℃ / min and maintain for 6h under nitrogen atmosphere. Control the pressure at 2MPa. Release the pressure after the reaction is completed. After the temperature cools down, take out the liquid phase as the thermal polycondensation oil product.
[0093] Step 2: Solvent extraction. The extractant is mixed at a mass ratio of n-octane to furfural of 1.25:2; the heat-condensed oil and the extractant are stirred and mixed at a mass ratio of 1:1.25, and fully mixed at 60°C and allowed to stand for stratification. The lower layer of the extract is slowly heated to 140°C and the "enriched aromatic oil" is obtained under a vacuum of 150Pa.
[0094] Step 3: Template-induced carbonization treatment The same method as the third step in Example 4 was used, except that the hard template used was nano-magnesium oxide with a particle size of 50 nm.
[0095] Step 4: Pickling, water washing and vacuum drying to obtain graphene material. The same method as the fourth step in Example 1 is used, except that the mass ratio of hydrochloric acid to magnesium oxide added during pickling is 2:1.
[0096] The obtained porous graphene was subjected to scanning electron microscope analysis to observe the morphology and transmission electron microscope analysis to observe the thickness of the sheet. The results are shown in FIG4. Figure 4a and Figure 4b It can be seen that the porous graphene generated by the "aromatic-enriched oil" used in this example under the carbonization induced by nano-magnesium oxide hard template presents a continuous spherical or cylindrical hollow three-dimensional structure, with more wrinkles than when zinc oxide is used as a template, but still significantly less than when iron oxide is used as a template; through further magnification observation, such as Figure 4c-1 and Figure 4c-2 It can be more clearly seen that the thickness of the thin layer is between 2-4nm.
[0097] Example 5
[0098] Step 1: High-temperature pretreatment of crude oil. Take 520g of catalytic cracking oil slurry and put it into a high-temperature reactor. Raise the temperature to 420℃ at 5℃ / min and maintain for 2h under nitrogen atmosphere. Control the pressure at 3MPa. Release the pressure after the reaction is completed. After the temperature cools to room temperature, take out the liquid phase as the thermal polycondensation oil product.
[0099] Step 2: Solvent extraction. The extractant is mixed at a mass ratio of n-octane to furfural of 1.25:2; the heat-condensed oil and the extractant are stirred and mixed at a mass ratio of 1:1.5, and fully mixed at 70°C and allowed to stand for stratification. The lower layer of the extract is slowly heated to 140°C and the "enriched aromatic oil" is obtained under a vacuum of 150Pa.
[0100] Step 3: Template-induced carbonization treatment: The same method as the third step in Example 1 is used for the treatment.
[0101] Step 4: Acid washing, water washing and vacuum drying to obtain graphene material. The same method as the fourth step in Example 1 is used.
[0102] The obtained porous graphene was subjected to scanning electron microscope analysis to observe the morphology and transmission electron microscope analysis to observe the thickness of the sheet. The results are shown in FIG5. Figure 5a and Figure 5b It can be seen that the porous graphene structure generated by the "aromatic-enriched oil" used in this example under the nano-iron trioxide hard template induced carbonization is not much different from the graphene structure prepared in Example 1, mainly because the carbon source structure used is similar and the type and amount of template agent added are the same.
[0103] Comparative Example 1
[0104] This comparative example only provides a comparative explanation for the crude oil pretreatment step.
[0105] High-temperature pretreatment of crude oil. Take 520g of catalytic cracking oil slurry and put it into a high-temperature reactor. Raise the temperature to 400℃ at 5℃ / min and maintain for 10h under nitrogen atmosphere. Control the pressure at 2MPa. Release the pressure after the reaction is completed. After the temperature cools to room temperature, take out the liquid phase as the thermal polycondensation oil product.
[0106] When the reaction time was extended to 10h, the saturated fraction in the polycondensation oil composition was significantly reduced to 11.6%, but the aromatic fraction was not significantly increased compared with the raw oil, the asphaltene and resin fractions increased significantly, and the oil phase yield was only 32.7%.
[0107] The four components, simulated distillation and yield results of the "thermal polycondensation oil" obtained by treatment were analyzed. When the heat treatment temperature was increased to 400℃ and the heating time was as long as 10h, the saturated content in the product decreased to 11.66, but the aromatic content also decreased to 28.59; at the same time, the yield was only 32.7%.
[0108] Comparative Example 2
[0109] This comparative example only provides a comparative explanation for the crude oil pretreatment step.
[0110] High-temperature pretreatment of crude oil. Take 520g of catalytic cracking oil slurry and put it into a high-temperature reactor. Heat it to 420℃ at 5℃ / min and maintain it for 6h under nitrogen atmosphere. The pressure is controlled to 0MPa. After the reaction is completed, release the pressure and take out the heat-condensed oil product after the temperature cools to room temperature.
[0111] When the reaction temperature was increased to 420°C, the time was extended to 6h, and the pressure was reduced to 0MPa, the saturated content in the polycondensation oil composition was significantly reduced to 11.6%, but the aromatic content was not significantly increased compared with the raw oil, the asphaltene and resin parts increased significantly, and the oil phase yield was only 9.5%.
[0112] The four components, simulated distillation and yield results of the "thermal polycondensation oil" obtained by treatment were analyzed. When the heat treatment temperature was increased to 420℃ and the heating time was as long as 6h, although the reaction pressure was adjusted to 0MPa, the aromatic content of the product decreased to 24.11; at the same time, the oil phase yield was only 9.5%, and the rest was converted into solid coke or sticky coke.
[0113] Comparative Example 3
[0114] This comparative example only provides a comparative explanation for the crude oil pretreatment step.
[0115] High-temperature pretreatment of crude oil. Take 520g of catalytic cracking oil slurry and put it into a high-temperature reactor. Raise the temperature to 420℃ at 5℃ / min and maintain for 10h under nitrogen atmosphere. Control the pressure to 0MPa. Release the pressure after the reaction is completed, and take out the heat-condensed oil product after the temperature cools to room temperature.
[0116] When the reaction temperature is increased to 420°C, the reaction time is extended to 10 hours, and the pressure is reduced to 0 MPa, almost no oil phase is produced, the catalytic oil slurry is completely cracked, and the remaining part is completely converted into solid coke or sticky coke products.
[0117] Comparative Example 4
[0118] This comparative example only provides a comparative explanation for the template induction step.
[0119] The first step: high temperature pretreatment of crude oil is carried out in the same manner as the first step in Example 3.
[0120] Step 2: Solvent extraction: The same method as the second step in Example 3 is used for the extraction.
[0121] Step 3: Template-induced carbonization treatment: The same method as the third step in Example 3 is used, except that the "enriched aromatic oil" and the nano-iron trioxide template are fully mixed in a mass ratio of 1:1.
[0122] Step 4: acid washing, water washing and drying to obtain graphene material. The same method as the fourth step in Example 3 is used for the implementation.
[0123] The morphology of the prepared porous graphene was observed by electron microscope scanning analysis. Figure 6 As shown, from Figure 6 It can be seen that the "aromatic-enriched oil" used in this example does not generate a porous graphene structure when carbonized by inducing carbonization with only a 1:1 addition of the nano-ferric oxide hard template. Due to the small amount of template agent, a large number of carbon layers are connected together, and the template agent does not play a role in morphology construction.
[0124] Table 1 Analysis results of four components, yield and distillation range distribution of the heat-condensed polyol obtained in Examples 1-5 and Comparative Examples 1-3
[0125]
[0126] Table 2 Four components and yield analysis results of the enriched aromatic oil obtained in Examples 1-5
[0127]
[0128] As can be seen from Table 1, the method of the present invention regulates the molecular structure of the catalytic oil slurry through thermal polycondensation treatment, so that the saturated side chains that are easy to crack are broken and removed, thereby reducing the content of saturated components; the macromolecular condensed aromatic hydrocarbons with cycloalkane rings and side branches that are easy to crack are further broken to form small molecular aromatic hydrocarbons, and the high-condensation macromolecular condensed ring components that are easy to coke are coked, thereby increasing the overall aromatic content.
[0129] As shown in Table 2, the method of the present invention further enriches aromatics through solvent extraction, and uses the extracted oil, i.e., aromatics-enriched oil, as a carbon source to improve the reactivity of the raw material molecules in preparing graphene materials. In addition, by mixing with a hard template, the aromatic molecules are self-assembled and grown into carbon materials through the skeleton and growth sites provided by the hard template agent during high-temperature treatment, and finally the template agent is removed by acid washing to obtain a three-dimensional structured thin-layer graphene material.
[0130] In summary, the present invention takes the characteristics of catalytic oil slurry as raw material, efficiently separates the aromatic components therein through heat treatment and solvent extraction treatment, uses the treated catalytic oil slurry as a carbon source, uses nano-metal oxide as a template and pore-forming agent, and prepares a graphene material with a thin layer three-dimensional structure through carbonization treatment in an inert atmosphere. In addition, the method has a simple process, low raw material price, and controllable structure of the graphene material, and has a good market prospect for large-scale application.
[0131] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the present invention.
Claims
1. A method for preparing graphene material from catalytic oil slurry, characterized in that: The steps include: (1) subjecting the catalytic oil slurry to a thermal polycondensation treatment under the protection of an inert gas atmosphere, and taking out the liquid phase after cooling as the thermal polycondensation oil; (2) mixing the polycondensed oil with an extractant for extraction and separation, allowing the oil to stand for stratification after extraction, taking the lower layer, and evaporating the extractant in the lower layer to obtain an enriched aromatic oil, wherein the extractant is composed of furfural and n-octane; (3) After the enriched aromatic oil and the template are fully mixed in the presence of an organic solvent as an auxiliary agent, the organic solvent is evaporated and then carbonized in an inert gas atmosphere; (4) The carbonized product obtained in step (3) is subjected to acid washing to remove the template agent, washed with deionized water and then dried to obtain a porous graphene material.
2. The method according to claim 1, characterized in that The drying in step (4) is vacuum drying; stirring is also performed in step (1), and the stirring speed is not less than 150 revolutions per minute.
3. The method according to claim 2, characterized in that The stirring speed is greater than 200 revolutions / min.
4. The method according to claim 2, characterized in that: The stirring speed is 200-500 rpm.
5. The method according to claim 1, characterized in that: The saturated content of the heat-condensation polyol is less than 18 wt %, the aromatic content is greater than 45 wt %, and the fraction below 520° C. is greater than 50 wt %.
6. The method according to claim 1, characterized in that The conditions of the thermal polycondensation treatment are: temperature 380-420° C., pressure 2-7 MPa, and time 2-10 hours.
7. The method according to claim 6, characterized in that The temperature of the thermal polycondensation treatment is 380-400°C.
8. The method according to claim 6, characterized in that The temperature rise program of the thermal polycondensation treatment is any one of the following: (1) 5~10℃∙min -1 Heating to 350℃, 3℃∙min -1 Rapidly heat to 380℃ within 10min, keep warm for 6~10h, pressure 3~5MPa; (2) 5~10℃∙min -1 Heating to 350℃, 5℃∙min -1 Rapidly heat to 400℃ within 10min, keep warm for 2~6h, pressure 2~6MPa; (3) 5~10℃∙min -1 Heating to 350℃, 7℃∙min -1 Rapidly heat to 420°C within 10 minutes, keep warm for 1.5-3.0 hours, and keep the pressure at 2-4 MPa.
9. The method according to claim 1, characterized in that: The mass ratio of n-octane:furfural is 1:2~2:
2.
10. The method according to claim 9, characterized in that The mass ratio of n-octane:furfural is 1.5:
2.
11. The method according to claim 1, characterized in that: The mass ratio of the extractant to the thermal polycondensation oil is 1:1 to 2.5:
1.
12. The method according to claim 11, characterized in that The mass ratio of the extractant to the thermal polycondensation oil is 1.25:1 to 2:
1.
13. The method according to claim 1, characterized in that The extraction temperature is 50-90°C.
14. The method according to claim 13, characterized in that The extraction temperature is 60-70°C.
15. The method according to claim 1, characterized in that In the enriched aromatic oil, the saturated fraction is less than 5 wt%, the aromatic fraction is greater than 80 wt%, and the asphaltenes are less than 2 wt%.
16. The method according to claim 1, characterized in that The template is metal oxide nanoparticles with a particle size of 30-200 nm.
17. The method according to claim 16, characterized in that The template agent is nano iron oxide, nano magnesium oxide or nano zinc oxide, and its particle size is 80-150nm.
18. The method according to claim 1, characterized in that The mass ratio of the template to the enriched aromatic oil is 3:1 to 5:
1.
19. The method according to claim 1, characterized in that The organic solvent is selected from one of toluene, xylene, carbon disulfide and carbon tetrachloride, and the volume ratio of the organic solvent to the enriched aromatic oil is 0.3-1.0:
1.
20. The method according to claim 1, characterized in that The organic solvent is toluene.
21. The method according to claim 1, characterized in that The heating rate of the carbonization treatment is 5-10°C / min, the carbonization temperature is 700-900°C, and the carbonization time is 1-3h.
22. The method according to claim 1, characterized in that The inert gas is nitrogen or argon.
23. The method according to claim 1, characterized in that The acid used for pickling is hydrochloric acid, sulfuric acid or nitric acid, and the mass ratio of the acid to the template is 3:1 to 1:
1.
24. The method according to claim 1, characterized in that The porous graphene material is a three-dimensional structure in the form of a porous thin shell with a wall thickness of only 2 to 4 nm and a number of layers of less than 10.